Cover Image. Issue 3 (27th February 2018) - Jeon, Y. J.; Lim, J. H.; An, S.; Jo, A.; Han, D. H.; Won, T.‐B.; Kim, D.‐Y.; Rhee, C.‐S.; Kim, H. J.
Abstract : The cover image, by Y. J. Jeon et al., is based on the Original Article Type III interferons are critical host factors that determine susceptibility to Influenza A viral infection in allergic nasal mucosa, DOI:10.1111/cea.13082 .